A Percutaneous Threaded Wire as a Clamp Technique for Avoiding Wedge Deformity While Nailing Intertrochanteric Femur Fractures. Issue 7 (July 2019) - Maupin, Jeremiah J.; Steinmetz, Raymond G.; Hickerson, Lindsay E.
Abstract : Summary: Hip fractures are common injuries managed by the orthopaedic surgeon, and within the umbrella of hip fractures, intertrochanteric femur fractures constitute a significant portion of these injuries. Recent trends have shown an increased usage of cephalomedullary nails for these injuries. A known potential complication of this technique is the generation of a wedge deformity creating a varus alignment, especially when the cranial portion of the intertrochanteric fracture exits at or near the starting point of the nail. Although the biomechanics of this phenomenon are well described, few reports have shown techniques to help avoid this phenomenon. Here, we present a novel technique we have found useful to help prevent the wedge deformity incorporating commonly available instruments.